Penguatan Profil Pelajar Pancasila Berdasarkan Landasan Filosofis Belalek Pada Masyarakat Melayu Sambas - Dendodi Dendodi; Aunnurrahman Aunnurrahman; Halida Halida (Departement of Mathematics Education, 2023)
Belalek is a basic term used by the Sambas Malay community to refer to the word mutual cooperation , the word belalek usually specifically refers to agricultural activities, but in general the word belalek has a broad meaning which includes aspects of an attitude of cooperation and togetherness. Belalek cultural tradition activities have been around for a long time and there are social values and local wisdom which aim to develop the value of mutual cooperation and the value of solidarity which can be implemented in schools to strengthen the profile of Pancasila students. This research was designed using qualitative research methods using a library research approach . Apart from this method, the researcher also used an interview method with one of the residents of the Sambas Malay tribe, namely a resident of Tri Kembang Village, Galing District, regarding the philosophical basis of Belalek which is closely related to the independent curriculum, especially in developing an attitude of mutual cooperation in students. So that the strengthening values of the Pancasila student profile are varied, such as mutual concern, harmony in society, discipline, moral education, leadership and so on, all of which are included in in aspects of the philosophical foundations of Belalek